2022
DOI: 10.1039/d2ob01075e
|View full text |Cite
|
Sign up to set email alerts
|

The role of Na+ in catalysis by the 8–17 DNAzyme

Abstract: The 8-17 DNAzyme is the most studied deoxyribozyme in terms of its molecular mechanism, hence it has become a model system to understand the basis behind DNA catalysis. New functional...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…As shown in Figure 7 , the positively cooperative role of Na + is significant in the case of Pb 2+ -, Zn 2+ -, and Mn 2+ -assisted reactions, but not in the case of Ca 2+ and Mg 2+ . A similar contribution of Na + was also observed for the 8-17 DNAzyme [ 35 ]. Na + was supposed to play a promotive role, probably by strengthening the electrostatic interaction within the catalytic residue–metal ion complex [ 19 ].…”
Section: Resultssupporting
confidence: 79%
“…As shown in Figure 7 , the positively cooperative role of Na + is significant in the case of Pb 2+ -, Zn 2+ -, and Mn 2+ -assisted reactions, but not in the case of Ca 2+ and Mg 2+ . A similar contribution of Na + was also observed for the 8-17 DNAzyme [ 35 ]. Na + was supposed to play a promotive role, probably by strengthening the electrostatic interaction within the catalytic residue–metal ion complex [ 19 ].…”
Section: Resultssupporting
confidence: 79%
“…The 8-17 DNAzyme is one of the most studied DNAzymes in terms of structure and mechanism. [28][29][30][31] Its three-dimensional structure in the presence of an uncleavable substrate was determined by X-ray crystallography, 32 further confirming its compact structure. To endow the metal-responsiveness to the 8-17 DNAzyme, we employed the artificial Im C -Cu II -Im C base pair, which is one of the metal-mediated base pairs with the greatest stabilizing effect.…”
mentioning
confidence: 88%
“…Another study showed that the insertion of a C3 spacer in the catalytic core did not corrupt 39E activity but enhanced about 10–fold UO 2 2+ –sensitivity [ 29 ]. Some simulation works also investigated the effects of pH values and monovalent metal ions on the activities of DNAzymes [ 26 , 27 , 30 , 31 ]. These suggest that DNAzymes might adopt much more complicated configuration arrangements toward the catalytic functions.…”
Section: Introductionmentioning
confidence: 99%